Functional Pseudotyping of Human Immunodeficiency Virus Type 1 Vectors by Western Equine Encephalitis Virus Envelope Glycoprotein - Poluri, Ananthalakshmi (American Society for Microbiology (ASM), 2008)
We investigated the ability of western equine encephalitis virus envelope glycoproteins (WEEV GP) to pseudotype lentiviral vectors. The titers of WEEV GP-pseudotyped human immunodeficiency virus type 1 (HIV) ranged as high as 8.0 × 10(4) IU/ml on permissive cells. Sera from WEEV-infected mice specifically neutralized these pseudotypes; cell transduction was also sensitive to changes in pH. The host range of the pseudotyped particles in vitro was somewhat limited, which is atypical for most alphaviruses. HIV vectors pseudotyped by WEEV GP may be a useful tool for characterizing WEEV cell binding and entry and screening for small-molecule inhibitors.